PRESCRIPTION PATTERN ANALYSIS OF NON-STEROIDAL ANTI-INFLAMMATORY DRUGS IN TERTIARY CARE HOSPITAL - INAMDAR, ZEBA; SN, SARWAMANGALA; V, PADMAVATI; DALAL, VARSHA I; N BALI, PRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the study was to analyze the prescription pattern of non-steroidal anti-inflammatory drugs (NSAIDs) and to identify the commonly used NSAIDs and their drug-related problems (DRPs). Methods: A prospective and cross-sectional study on prescription pattern analysis of NSAIDs was conducted for the period of 6 months. Results: Prescriptions of 150 patients containing at least one NSAIDs were analyzed. About 56% of the prescription were prescribed for males and 44% prescription were female. NSAIDs were more prescribed for below 60-year age group (47%) but were most frequently used by 61–70-year age group (21%). Subjects were regularly prescribed with acetaminophen (95%) and diclofenac (22%). Among all the prescriptions, (19%) of the prescriptions contained NSAIDs in the form of fixed dose combinations (FDCs). About 37% of prescriptions had other analgesic coprescribed along with NSAIDs amid which tramadol was in majority (22%). Prescription was also coprescribed with antibiotic (90%) and gastroprotective agents (GPAs) (97%) that consisted of pantoprazole belonging to the class of proton pump inhibitors which was the persistently prescribed GPA (86%). Due to coprescription, (3%) suspected drug-drug interactions (DDIs) were observed. Conclusion: The goal of studying prescribing patterns was to monitor, assess, and, if required, advise changes in medical practitioners’ prescribing behavior to offer quality medical treatment and reasonable drug use. The prescribing pattern was rational and in accordance with national list of essential medicine (NLEM-2015) but was not in accordance with the World Health Organization (WHO) model list of essential medicines.